Mediated Dispute Resolution in the Distribution of Outsourced Labor in the Gili Tramena Area - Rahmawati Kusuma; Zaeni Asyhadie (JILPR Journal Indonesia Law and Policy Review, 2023)
This research aims to determine how the resolution of labor disputes through mediation in the outsourcing workforce distribution in the Gili Tramena (Trawangan, Meno and Air) tourism area, as well as the factors influencing the effectiveness of labor dispute resolution through mediation in the outsourcing workforce distribution. The legal status between workers and employers in an employment relationship is said to be the same, but empirically, this juridical fact is difficult to establish. In employment relationships, employers are often "perceived" to have a higher status than workers, leading to inequalities and misunderstandings. The issues to be discussed in this research are how labor dispute resolution through mediation in the outsourcing workforce distribution in the Gili Tramena tourism area and the factors influencing labor dispute resolution through mediation in the outsourcing workforce distribution in the Gili Tramena tourism area. This research is expected to provide positive benefits for the development of teaching materials for the Labor Law course at the Faculty of Law, University of Mataran, including enhancing the literature or references for the relevant course. In practical terms, the results of this research are expected to provide input to relevant parties on the methods of labor dispute resolution through mediation in the outsourcing workforce distribution.